2021
DOI: 10.1073/pnas.2023659118
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic basis of propofol-induced disruption of kinesin processivity

Abstract: Propofol is a widely used general anesthetic to induce and maintain anesthesia, and its effects are thought to occur through impact on the ligand-gated channels including the GABAA receptor. Propofol also interacts with a large number of proteins including molecular motors and inhibits kinesin processivity, resulting in significant decrease in the run length for conventional kinesin-1 and kinesin-2. However, the molecular mechanism by which propofol achieves this outcome is not known. The structural transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…, 2017 ; Woll et al. , 2018 ; Dutta et al. , 2021 ), we used a labeling strategy that we recently developed to visualize vesicle-bound Kinesin-1 family member KIF5C ( Yang et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2017 ; Woll et al. , 2018 ; Dutta et al. , 2021 ), we used a labeling strategy that we recently developed to visualize vesicle-bound Kinesin-1 family member KIF5C ( Yang et al.…”
Section: Resultsmentioning
confidence: 99%
“…Further work found that propofol reduces run lengths by binding to the leading head of microtubule-bound kinesins, increasing the probability of dissociation before the lagging head can complete a step ( Woll et al. , 2018 ; Dutta et al. , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular underpinnings of allosteric changes in protein structures are often hindered by averaged metrics, the transient nature of the species involved (8), the difficulty to reproduce biological events in vitro (9), or the great deal of computational power required to model uncharted free-energy surfaces (9,10). Nonetheless, allosteric regulations are widespread in biology (11)(12)(13)(14)(15)(16)(17)(18), and the characterization of the underlying free energy is critical to understand and control the functional conformational landscape of biomolecules (19). The objective of this work is thus to devise a computational procedure to efficiently explore the functional freeenergy landscape of a protein with and without the allosteric effector bound, thereby gaining insight into how conformational equilibria translates into function.…”
Section: Introductionmentioning
confidence: 99%
“…Propofol is an intravenous general anesthetic widely used for general anesthesia and for sedation in ICU [10]. Propofol acts by binding to and modulating several neuronal ion channels and its effects are thought to occur through an impact on the ligand-gated channels including the GABA A receptor [11].…”
Section: Introductionmentioning
confidence: 99%